The Influence of Background Knowledge on Students’ Translation Results: An Interlingual Translation - Abdurrahman Hi. Usman; Suratman Dahlan; Abdulhalim Daud; Adi F. Mahmud (Journal of Languages and Language Teaching, 2022)
This research aims to identify whether students’ background knowledge influenced the translated texts from the source language (SL) into the target language (TL). This research employs descriptive qualitative method design throught the use of semi-structured interviews and observation in one of the state universities in east Indonesia. The participants in this research included 30 students. The documents as students' target texts were used as primary data and the transcripts of semi-structured interviews were used as supporting data. To Analyse the data, the researchers used qualitative ways. Data condensation, data display, and conclusion drawing or verification were used to reveal students’ background knowledge of translation. The data showed that most of the students need background knowledge in the translation of source language into the target language. These reasons confirm that there is a close relationship between background knowledge and translation. It means that in an interlingual translation, even if translators are bilinguals and master the grammar of a language, background knowledge of a text should also be dominated. Moreover, background knowledge is not a single problem for translators, there are also other problems that were found in students’ translation namely new words, complex sentences, reading comprehension, and expression in the target language.